The Effect of Cool Roof System on Surface and Indoor Temperature for Residential House in Malaysia: Field Measurement on Small Scale Model - Lawin, Keane Aldrige; Zakaria, Mohd Azuan (Recent Trends in Civil Engineering and Built Environment, 2024)
High indoor environment causes passive and cooling methods used in residential buildings is getting more attention in hot climate countries such as Malaysia. A hot indoor environment causes the occupants to use air conditioning to improve indoor thermal comfort. Thus, this will be resulting in high consumption of energy. This study investigates various existing cooling strategies then compares their effectiveness to reduce heat gain through the roof in low rises building in Malaysia. A measurement field will be conducted on a small-scale model house located in open spaces University Tun Hussein Onn Malaysia, Parit Raja, Batu Pahat, Johor, Malaysia. The material used for this small-scale model is cement board, aluminum frame, and roof tile, while other cases are included with insulation and reflective material. The sensors are placed in the attic space, ceiling surface, and indoor to obtain indoor and surface temperature. The data collection are taken at least three days, depending on the weather. The result shows that the ventilated model is the coolest with the differences value of 15.7°C attic temperature, 11.8°C ceiling temperature, and 4.8°C indoor temperature, compared with the control model among the cases. When compared the cases with the outdoor temperature double roof model is better temperature with the range of (-1°C to 2°C) for attic, while for ceiling temperature are( -5°C to 3°C) and the indoor temperature are (-4°C to 0°C). For the night and day comparison with the control model, ventilated model reduced the temperature of the attic by -17.07°C, ceiling surface by -14°C, and indoor at -5.3°C. The data educed by the ventilated model are -16.46°C for attic, -11.8°C for ceiling surface, and indoor temperature with -3.8°C. In conclusion, double roof systems were identified as a system able to reduce indoor temperature to comfortable temperature and energy saving for lack of dependencies on mechanical cooling.